THE INFLUENCE OF EMOTIONAL BRANDING, PERSONAL SELLING AND ELECTRONIC WORD OF MOUTH ON CONSUMER LOYALTY OF VASELINE PRODUCTS - Fransiska Mariana Unenor; Nadia Sasmita Wijayanti; Yonas F. Riwu (RADJA PUBLIKA, 2025)
The aim of this research is to find out how consumers loyalty to Vaseline goods is affected in the Kupang City neighborhood via emotional branding, human selling, and electronic word-of-mouth. The study uses an associative technique and a quantitative survey method. Data were collected with a survey table of 100 respondents of Vaseline product consumers in Kupang City. The primary data obtained were processed using the SPSS application. The technique for collecting data involved distributing questionnaires, while the method used for data analysis was multiple linear regression, with hypothesis testing conducted in conjunction with the F-test, t-test, and the coefficient of determination (R2) test. The findings showed that, while emotional branding had no discernible impact on customer loyalty, Both electronic and human word-of-mouth marketing had a favorable and considerable impact. Furthermore, it was discovered that customer loyalty was significantly impacted by the three independent variables taken together. According to the coefficient of determination (R2), consumer characteristics may be explained by the elements of digital word-of-mouth, personal selling, and emotional branding. The study's conclusions also provide valuable information for Kupang City's Vaseline product marketing plan. Companies need to focus on personal selling and electronic word of mouth because they have been proven to increase consumer loyalty. Conversely, the emotional branding strategy needs to be evaluated because it has not had a significant impact.